1996
DOI: 10.1080/02688699647339
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopy-assisted burr hole evacuation of subdural empyema

Abstract: A 71-year-old man developed a large multi-loculated subdural empyema following the evacuation of a chronic subdural haematoma. The pockets of pus were successfully evacuated endoscopically via the burr holes resulting in good recovery and no re-accumulation. The advantages of this technique and the difficulties encountered during this procedure are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Successful evacuation of subdural haematomas, pus as well as hygromas have been achieved with the use of endoscopic [ 21 , 47 , 48 ]. The endoscope assists in the assessment of the subdural space to ensure satisfactory clot evacuation as well as haemostasis, and to incise abnormal membranes as well as trabecula in instances of loculated CSDHs [ 21 , 28 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Successful evacuation of subdural haematomas, pus as well as hygromas have been achieved with the use of endoscopic [ 21 , 47 , 48 ]. The endoscope assists in the assessment of the subdural space to ensure satisfactory clot evacuation as well as haemostasis, and to incise abnormal membranes as well as trabecula in instances of loculated CSDHs [ 21 , 28 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Successful evacuation of subdural haematomas, pus as well as hygromas have been achieved with the use of endoscopic [ 21 , 47 , 48 ]. The endoscope assists in the assessment of the subdural space to ensure satisfactory clot evacuation as well as haemostasis, and to incise abnormal membranes as well as trabecula in instances of loculated CSDHs [ 21 , 28 , 47 , 48 ]. Furthermore, during the procedure, the surgeon is able to irrigate the hematoma cavity, insert a drainage tube toward the frontal convexity to evacuate subdural air, avoid cortical laceration that often happen as result of blind manipulation, coagulate the source of bleeding as well as separate the inner membrane carefully to aid in brain expansion [ 22 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscope-assisted burr hole evacuation of subdural collections has previously been performed in the settings of chronic and subacute SDH, 8,21,23 subdural hygroma, 22 and subdural empyemas. 15 Mobbs and Khong 23 and Codd et al 4 demonstrated a similar 2-burr-hole approach to treat these subdural collections. However, it is important to distinguish an acute SDH from its chronic liquefied counter-parts.…”
Section: Acute Subdural Hematomasmentioning
confidence: 99%
“…3 In recent studies, it is noteworthy that the use of endoscopy has become widespread in the surgery of ASDH, 2,4-9 CSDH [10][11][12][13][14] and subdural collections such as subdural empyema. 15 There were many cases of subdural hematoma as performed with rigid endoscopes, 2,[4][5][6][7][8][9][10][11][12] and the authors commonly prefer the center or the thickest site of the hematoma as the entrance point. However, because of the inflexible nature of rigid endoscopes, the optimal location of the craniotomy may not be the center or thickest part of the hematoma in order to evaluate the surgical area in an extensive range.…”
mentioning
confidence: 99%